Social media in Kazakhstan (Herald of Journalism, 2018)
In the article of Myssayeva K.N. “Social Media in Kazakhstan” examines the development of socialmedia in Kazakhstan. The main purpose of social media is communication, reflection and organizationof social relationships on the Internet. Special attention is given to the development and role of socialmedia on society.